Pengaruh Coding Game Terhadap Kemampuan Problem Solving Anak Usia Dini - Ubaidillah, Ubaidillah; Setiarini, Nur; Budiarti, Iin; Windarty, Krista (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the effect of implementing visual-based coding games on the problem-solving abilities of children aged 5–6 years at TK Muslimat NU 9 Sekar Kedaton. A quasi-experimental method with a pretest-posttest control group design was employed. The subjects consisted of 28 children divided into an experimental group (14 children) and a control group (14 children). The experimental group received an eight-week intervention using the ScratchJr application, while the control group engaged in conventional physical activity-based learning. Data were collected through participatory observation using the Problem Solving Observation Checklist (PSOC) adapted from Bers (2018) and a scenario-based task test. Data analysis was conducted using the Wilcoxon Signed Rank Test. The results showed a significant improvement in the experimental group (Z = -3.21; p < 0.01), with an average score increase of 42%, compared to only 12% in the control group. The study concludes that coding games enhance children’s problem-solving abilities systematically and support the development of Islamic values such as collaboration and perseverance in the learning process